Targeting the dual miRNA/BMP2 network: LncRNA H19-mediated temozolomide resistance unveils novel therapeutic strategies in glioblastoma - Qiudan Chen; Shihao Zhuang; Shuying Chen; Biying Wu; Qingyu Zhou; Weifeng Wang (Frontiers in Oncology)
BackgroundLong noncoding RNA (lncRNA) is known to not only be involved in various biological processes but also to play a crucial role in chemotherapy resistance. The development of resistance in glioblastoma (GBM) poses a significant challenge in clinical settings. Nonetheless, the mechanisms through which lncRNA contributes to acquired resistance to Temozolomide (TMZ) in GBM patients remain unclear.MethodsWe identified 265 upregulated and 396 downregulated lncRNAs associated with chemoresistance in GBM from the GEO database (GSE100736). Subsequently, we assessed the expression levels of lncRNA H19, hsa-miR-138-5p, hsa-miR-22-3p, and BMP2 mRNA through quantitative polymerase chain reaction (qPCR) in GBM cells and TMZ-resistant GBM cells. Cell viability and proliferation were evaluated using CCK-8 and cell colony formation assays, respectively. Apoptosis was determined through flow cytometry analysis. The impact of gene overexpression and knockdown on cell proliferation and apoptosis was examined via cell transfection experiments. Furthermore, we investigated the influence of lncRNA H19 on tumor development using an in vivo xenograft tumor model.ResultsThe upregulation of lncRNA H19 was observed in TMZ-resistant GBM cell lines and tissues, suggesting its involvement in acquired TMZ resistance. Silencing lncRNA H19 restored TMZ sensitivity in resistant GBM cells in vitro. Conversely, overexpression of lncRNA H19 promoted GBM cell proliferation and hindered TMZ-triggered apoptosis, facilitating the acquisition of TMZ resistance. Notably, lncRNA H19 functions as a molecular decoy for hsa-miR-138-5p and hsa-miR-22-3p, and these miRNAs can reverse the acquired TMZ resistance induced by lncRNA H19 in GBM cells. Additionally, BMP2 gene expression is crucial in the lncRNA H19-mediated pathway of acquired TMZ resistance in GBM cells. Knockdown of lncRNA H19 reinstated TMZ sensitivity in vivo, whereas BMP2 overexpression reinstated TMZ resistance.ConclusionLncRNA H19 enhances TMZ resistance in glioblastoma through competitive RNA targeting of BMP2.